Deterministic and probabilistic models for the estimation of nitrate loads in a rural basin - Gelmi, Mónica E.; Seoane, Rafael S. (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
In this work a new probabilistic model was developed. The new model applies the derived density function theory to estimate nitrate mean annual load transported by surface runoff. A functional relationship between runoff and nitrate load was used. The deterministic hydrologic and water quality model Simulator for Water Resources in Rural Basins - Water Quality (SWRRB-WQ) was used to estimate nitrate load in surface runoff. This model uses, as input variable, daily precipitation observed at Olavarría Airport Meteorological Station, for the 1988-2002 period. For model calibration a new method that estimates uncertainty in observed values is applied. Both probabilistic and deterministic hydrologic models are applied in a rural subbasin of Tapalqué River (province of Buenos Aires, Argentina). Finally, estimated and observed nitrate loads are compared at the outlet section of the subbasin under study. The results of applying the selected probabilistic model show that the mean nitrate loads obtained, are of the same order of magnitude that the mean nitrate loads observed and estimated with the SWRRB-WQ hydrologic and water quality model.